2006
DOI: 10.1016/j.cell.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Protein Phosphatase 2A Core Enzyme Bound to Tumor-Inducing Toxins

Abstract: The serine/threonine phosphatase protein phosphatase 2A (PP2A) plays an essential role in many aspects of cellular functions and has been shown to be an important tumor suppressor. The core enzyme of PP2A comprises a 65 kDa scaffolding subunit and a 36 kDa catalytic subunit. Here we report the crystal structures of the PP2A core enzyme bound to two of its inhibitors, the tumor-inducing agents okadaic acid and microcystin-LR, at 2.6 and 2.8 A resolution, respectively. The catalytic subunit recognizes one end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
419
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(442 citation statements)
references
References 61 publications
(92 reference statements)
15
419
0
8
Order By: Relevance
“…The two Glu64 substitutions result in the inability of Aa to bind to the PR61/ B 0 a, g and d subunits, and the Arg418 and the frame-shift mutants display no binding to Ca and little or no binding to all B-type subunits [12,29,38]. These biochemical data can be explained in light of recent structural findings: Glu64 forms a hydrogen bond with the Ca C terminus, thereby stabilizing the A-PR61/B 0 g1 interface [36,37] (see Box 1, Figure Ib), Arg418 maps to the A-C interface and forms a hydrogen bond with Glu67 of Ca [34,36]. In addition, partial knockdown of the Aa subunit results in selective loss of PP2A holoenzymes containing the PR61/B 0 g subunit [29,30], rendering cells tumorigenic via increased Ser62 phosphorylation and stabilization of c-Myc [5,29,30].…”
Section: Reviewmentioning
confidence: 65%
See 3 more Smart Citations
“…The two Glu64 substitutions result in the inability of Aa to bind to the PR61/ B 0 a, g and d subunits, and the Arg418 and the frame-shift mutants display no binding to Ca and little or no binding to all B-type subunits [12,29,38]. These biochemical data can be explained in light of recent structural findings: Glu64 forms a hydrogen bond with the Ca C terminus, thereby stabilizing the A-PR61/B 0 g1 interface [36,37] (see Box 1, Figure Ib), Arg418 maps to the A-C interface and forms a hydrogen bond with Glu67 of Ca [34,36]. In addition, partial knockdown of the Aa subunit results in selective loss of PP2A holoenzymes containing the PR61/B 0 g subunit [29,30], rendering cells tumorigenic via increased Ser62 phosphorylation and stabilization of c-Myc [5,29,30].…”
Section: Reviewmentioning
confidence: 65%
“…33 No.3 previous biochemical and mutagenesis studies [1], the structure of Aa revealed that it binds to the Ca subunit via the intra-repeat loops of HEAT-repeats 11-15 (Box 1, Figure Ia), which causes a major conformational switch in Aa. This switch occurs mainly at the inter-repeat loops between repeats 11 and 12, and 12 and 13, resulting in a horseshoe-or C-shaped conformation of the Aa subunit [34]. The Ca subunit itself adopts an a/b fold typical of the serine/threonine-specific phosphoprotein phosphatase (PPP) family of phosphatases, which includes protein phosphatase 1 and calcineurin [35].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a series of recent reports on the 3D structures of multimeric forms of PP2A have had a major impact on our understanding of this important signaling molecule. A report by Shi and colleagues solved the structure of the AC core dimer bound to inhibitory toxins (4). Two additional papers, one by Cho and Xu (5) and a second from Shi and colleagues (6), coincidently report the structure of the same PP2A holoenzyme composed of the AC core dimer associated with the B56␥ regulatory subunit.…”
mentioning
confidence: 99%